2022
DOI: 10.1155/2022/5585384
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Heat Shock Protein 90 Attenuates the Damage of Blood-Brain Barrier Integrity in Traumatic Brain Injury Mouse Model

Abstract: Heat shock protein 90 (HSP90) is widely found in brain tissue. HSP90 inhibition has been proven to have neuroprotective effects on ischemic strokes. In order to study the role of HSP90 in traumatic brain injury (TBI), we carried out the present study. A novel inhibitor of the HSP90 protein, 17-dimethylaminoethylamino-17-demethoxygeldanamycin (17-DA), has been investigated for its function on the blood-brain barrier (BBB) damage after traumatic brain injury (TBI) in mouse models. These C57BL/6 mice were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We also found that KAE and PLA caused oxidative stress in A549 cells, leading to the generation of ROS and activation of NF-κB [ 43 ], a transcription factor involved in a variety of important processes, including inflammation, immunity, and tumour development. NF-κB is an important regulator of the production of inflammatory factors and, upon activation, enters the nucleus to regulate transcription and translation, including the increased content of NLRP3 proteins [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that KAE and PLA caused oxidative stress in A549 cells, leading to the generation of ROS and activation of NF-κB [ 43 ], a transcription factor involved in a variety of important processes, including inflammation, immunity, and tumour development. NF-κB is an important regulator of the production of inflammatory factors and, upon activation, enters the nucleus to regulate transcription and translation, including the increased content of NLRP3 proteins [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, blocking the HSP90 protein may be a potential therapeutic strategy for TBI. 35 HSP60 functions as an immunomodulatory molecule and a mitochondrial chaperone, thus it can activate the antigen-presenting cells of the immune system, including an auto-immunogen, at the site of inflammation. 36,37 Additionally, it becomes upregulated in reaction to mitochondrial impairment and is believed to be an indicator of mitochondrial stress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 17-AAG treatment attenuated endotoxin-induced vascular leakage in rat retinas [ 70 ]. Another Hsp90 inhibitor, 17-dimethylaminoethylamino-17-demethoxygeldanamycin (17-DMAG), blocked the disruption of the blood–brain barrier in a rat model of intracerebral hemorrhage [ 71 ], mouse models of cerebral ischemic stroke [ 72 ], and traumatic brain injury [ 73 ]. In these animal models, the attenuation of vascular permeability caused by Hsp90 inhibition was accompanied by the restored expression of key TJ proteins, such as occludin, ZO-1, and claudin-5 [ 70 , 71 , 72 , 73 ].…”
Section: Hspc/hsp90 Chaperonesmentioning
confidence: 99%
“…Similar to the described in vitro studies, in vivo protection of the vascular barriers is not a specific effect of Hsp90 inhibitors. Rather, it is a part of their general anti-inflammatory and tissue-protective activities that result in suppressed NF-kB signaling, decreased cytokine production, and upregulation of AKT activity [ 70 , 71 , 72 , 73 ].…”
Section: Hspc/hsp90 Chaperonesmentioning
confidence: 99%
See 1 more Smart Citation